1990
DOI: 10.1161/01.hyp.15.2_suppl.i76
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human mesangial cell proliferation by calcium channel blockers.

Abstract: Human mesangial cells in culture proliferate in response to platelet-derived growth factor (PDGF) and thrombin. Both of these agents also induce changes in cytosolic calcium that are dependent on both mobilization of intracellular calcium and influx of extracellular calcium. We hypothesized that calcium channel blockers, by preventing influx of extracellular calcium, may inhibit proliferation induced by these mitogens. We found that three different calcium channel blockers, diltiazem, nifediplne, and verapamil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
4

Year Published

1990
1990
2001
2001

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 14 publications
1
22
0
4
Order By: Relevance
“…6 Similar to renal vascular smooth muscle, it has been shown in contractile glomerular mesangial cells that Ca 2ϩ currents are only partially inhibited by antagonists of L-type Ca 2ϩ channels. 22 Ca 2ϩ influx through VDCCs has been suggested to be involved in mesangial cell growth, [23][24][25] which is important in pathological conditions such as diabetes mellitus and inflammatory glomerular diseases. Our demonstration of the expression of ␣ 1A subunit mRNA and protein in mesangial cells raises the possibility that P-/Q-type VDCCs may participate in mesangial cell function.…”
Section: Discussionmentioning
confidence: 99%
“…6 Similar to renal vascular smooth muscle, it has been shown in contractile glomerular mesangial cells that Ca 2ϩ currents are only partially inhibited by antagonists of L-type Ca 2ϩ channels. 22 Ca 2ϩ influx through VDCCs has been suggested to be involved in mesangial cell growth, [23][24][25] which is important in pathological conditions such as diabetes mellitus and inflammatory glomerular diseases. Our demonstration of the expression of ␣ 1A subunit mRNA and protein in mesangial cells raises the possibility that P-/Q-type VDCCs may participate in mesangial cell function.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, increases in the number of mesangial cells can also result in quantitative or qualita tive changes in the mesangial matrix proteins that are secreted by these cells and could contribute to glomeru losclerosis (9). Recently, Shultz et al (10) reported that Ca-channel blockers inhibited proliferation of human mesangial cells induced by PDGF or thrombin. Thus, the suppression of mesangial cell proliferation might have played a role in the protective effect of benidipine against the nephrotic syndrome.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, proliferation of mesangial cells decreases renal mass and induce a reduction in the glomerular fil tration rate (GFR). Recently, it was reported that Ca channel blockers inhibit human mesangial cell prolifera tion in vitro (10). These observations suggest that Ca channel blockers might have protective effects against renal injuries.…”
mentioning
confidence: 93%
“…Ca2'-channel blockers lower elevated blood pressure (10), inhibit the synthesis of DNA in VSMCs (11) and MCs (12), and reduce the development of atherosclerotic lesions in experimentally induced hypercholesterolemia (13). They may increase the glomerular ultrafiltration coefficient, which is limited, in part, by MC function, and stimulate the expression of the interleukin 6 (IL-6) gene (14).…”
Section: Introductionmentioning
confidence: 99%